Interculturality in criminal proceedings involving persons belonging to indigenous communities, peoples and nationalities of Ecuador - Núñez Castro, Wendy (Revista Universidad de Guayaquil, 2024)
Ecuador is a diverse country, characterized by its cultural diversity, which is why in the Magna Carta it has been constitutionally recognized as an intercultural country, thus obligating itself to respect interculturality in all areas that make up the State, including the legal field. The present study aims to demonstrate the need to include interculturality in the criminal process, for which the analytical method has been used to collect and analyze information related to interculturality and recognition of indigenous rights at the national and international level that allow us to guide ourselves in establishing why It is important to include interculturality in the criminal field. Deduction was also used to go from the general to the specific, moving through history until reaching the present in terms of indigenous rights, highlighting the importance of including interculturality and how that acts in the criminal process, resulting in that the inclusion of interculturality can become a real challenge, but if it does not do so, the State fails in this obligation of inclusion and respect of interculturality, violating the right to equality and defense. This study establishes the need to strengthen the justice system, so that it responds and promotes mechanisms that allow the effective development and fulfillment of the rights of indigenous people, allowing members of different cultures to actively participate in the criminal process. ensuring respect for their cultural identity, making the principle of equality effective and providing them with legal security.